OPTIMIZING INDEPENDENCE TRAINING THROUGH SEWING TRAINING AS AN EFFORT TO IMPROVE THE SKILLS OF PRISONERS AT THE CLASS IIA SALEMBA CORRECTIONAL INSTITUTION - Saragih, Erikson Candra; Soge, Markus Marselinus (Journal of Management Small and Medium Enterprises (SMEs), 2026)
Correctional institutions play an important role in equipping inmates with productive skills to support their reintegration into society. At the Class IIA Salemba Correctional Institution, one such effort is sewing skills training, which aims not only to improve work competence but also to foster discipline, independence, and readiness for social life after release. This study examines the optimization of self-reliance development through sewing training and identifies the obstacles faced in its implementation. Using a qualitative descriptive approach, data were collected through interviews, observations, and document analysis. The analysis is supported by optimization and skills development theories, with stages including data reduction, presentation, and conclusion drawing. The findings show that self-reliance development has been implemented through structured sewing training programs guided by supervisors and instructors. This approach helps inmates develop practical skills and work discipline. However, several challenges limit the program’s effectiveness, such as a lack of sewing machines, inconsistent training schedules, limited budgets, a shortage of skilled instructors, and the absence of post-release follow-up programs. These constraints reduce the long-term sustainability and impact of the training. Therefore, improvements in facilities, human resources, and continuity programs are necessary to optimize the benefits of sewing training for inmates’ future independence. Keywords: Self-Reliance Development; Sewing Training; Inmate Skills